Quantifying Bio-Engineering: The Importance of Biophysics in Biofuel Research - Varanasi, Patanjali; Sun, Lan; Knierim, Bernhard; Bosneaga, Elena; Sarkar, Purbasha; Singh, Seema; Auer, Manfred (IntechOpen, 2011)
None